Amplitude analysis of the B+ → D+D−K+ decay - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Dziewiecki, Michal; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review, 2020)
Results are reported from an amplitude analysis of the B+→D+D−K+ decay. The analysis is carried out using LHCb proton-proton collision data taken at √s=7, 8, and 13 TeV, corresponding to a total integrated luminosity of 9 fb−1. In order to obtain a good description of the data, it is found to be necessary to include new spin-0 and spin-1 resonances in the D−K+ channel with masses around 2.9 GeV/c2, and a new spin-0 charmonium resonance in proximity to the spin-2 χc2(3930) state.